Educating on democracy in a time of environmental disasters (UCL Press, 2021)
The recent diffusion of democracy across the globe has led to an increase in the curiosity of scholars, policymakers and the public alike about the main principles and characteristics of democracy. Equally important are concerns over outcomes of democracy, especially responsiveness of democracy to environmental and citizens' protection in times of disasters. This article aims to answer several questions about the understanding of principles and outcomes of democracy, and the complexity and variability of democracy across countries, which are still unanswered in the literature. Specifically, it adds to the scholarly debates on democracy and environmental disasters in three ways. First, it presents theoretical and empirical debates on definitions and principles of democracy and its progress worldwide. Second, it discusses the effect of democracy on environmental sustainability. Third, it focuses on the pre-eminence of responsiveness of democratic in comparison to non-democratic governments to environmental disasters, and the best pathways to education on democracy in a time of environmental disasters. The article concludes by highlighting the advantage of mechanisms and solutions of democracy in contrast to non-democracy to challenges in times of environmental disasters and to teaching about responses to environmental disasters.